Mathematical Reasoning of Prospective Mathematics Teachers in Solving Numeracy Problems - Agustin Fatmawati; Uke Ralmugiz; Nur Hasanah Syarief (Jurnal Inovasi Matematika, 2022)
Mathematical reasoning is one of the fundamental things in solving mathematical problems. This study was conducted aimed at describing the mathematical reasoning of students of the Mathematics Education study program in solving numeracy problems at the level of understanding, level of application, and level of reasoning. Numeracy questions were given to the research subjects and then interviews were conducted with 6 subjects. The data analysis techniques used follow the technical stages of data analysis including data condensation, data presentation, and drawing conclusions. The results showed that the activity at the formulating stage included the identification of significant variables and formulating mathematical situations using symbols. At the stage of working on the activity of the subject is to perform calculations and draw simple conclusions. Meanwhile, at the stage of interpreting and evaluating, the subject's activity is to evaluate mathematical results and interpret mathematical results into the context of the problem. At the level of application, Activities at the formulating stage include the identification of significant variables, making appropriate assumptions, translating problems into mathematical representations and recognizing aspects in the corresponding problem. The activity of the subject at the stage of work includes performing simple calculations, applying strategies for solving problems, and cultivating geometric representations. The activity of the subject at the stage of interpreting and evaluating includes the evaluation of mathematical results and interpreting the results into the context of the problem. At the level of reasoning activity at the formulating stage is to identify significant variables, understand and explain the relationship between the language of the context and the language of symbols, as well as represent the situation into the model. Activities at the stage of work include processing the information presented on the drawings to solve problems, performing calculations, drawing simple conclusions, and making generalizations.